Rancang Bangun Sistem Informasi Perkembangan Belajar Anak Berbasis Website - Yawa, Mareyke Kalasina (JATISI, 2024)
Early childhood education (ECE) is an important stage in child development that can have a long-term positive impact. Eden Tanjung Ria PAUD in Jayapura City understands the importance of developing children's potential early on and is committed to providing optimal educational services. However, parents' busy schedules cause a lack of monitoring of children's learning development. To overcome this problem, a web-based Child Learning Development Information System has been built that assists teachers in delivering real-time child learning development information to parents. This system uses PHP and MySQL with waterfall development method. The results show that this system makes it easier for teachers to record children's development and parents to monitor their children's learning progress. Hopefully, this system can improve the quality of preschool education by providing easy, fast, and transparent access to information for all related parties.